Metallic hydrogen with a strong electron-phonon interaction at a pressure of 300–500 GPa. (August 2017) - Degtyarenko, N.N.; Mazur, E.A.; Grishakov, K.S.
Abstract: Atomic metallic hydrogen with a lattice with FDDD symmetry is shown to have a stable phase under hydrostatic compression pressure in the range of 350–500 GPа. The resulting structure has a stable spectrum regarding the collapse of the phonons. Ab-unitio simulation method has been used to calculate the structural, electronic, phononic and other characteristics of the normal metallic phase of the hydrogen at a pressure of 350–500 GPA.